Common core literacy for math, science, and technical subjects : strategies to deepen content knowledge (grades 6-12) - McKnight, Katherine S. (Katherine Siewert); Staff Development for Educators (Company) (San Francisco, CA : Jossey-Bass, 2015)
'According to the Common Core State Standards, which have been adopted by 46 states, students must develop literacy skills not just in English/Language Arts but across all content areas. This means that educators must teach literacy--reading, writing, speaking, listening, and language--in subjects like Math, Science, Social Studies, and Technology/Computer Science. This book help teachers understand what literacy looks like in math, science, and technology classrooms and shows them how to develop these literacy skills in their students. Author Katie McKnight is a popular education consultant who trains teachers nationwide on Common Core literacy. Features include: Alignment of activities to the Common Core State Standards in Interdisciplinary Literacy Difficulty Dial: A quick reference to determine the complexity of each activity Tips for Classroom Implementation: An overview of each literacy activity and how the tool supports the development of literacy skills and builds content knowledge Student Samples: Useful references for teachers across subjects and grade levels'--
'This book helps teachers understand what literacy looks like in math, science, and technology classrooms and shows them how to develop these literacy skills in their students. The book shows teachers how to align their activities to the Common Core State Standards in Interdisciplinary Literacy, and it provides an overview of each literacy activity and how the tool supports the development of literacy skills and builds content knowledge'--
Chapter One. Why Does Content Literacy Matter? -- Chapter Two. Deepening Reading Comprehension Skills and Content Knowledge -- Chapter Three. Effective Content Area Writing Strategies -- Chapter Four. Speaking and Listening in the Content Area -- Chapter Five. Developing Academic Language -- Chapter Six. Learning Centers and Student-Centered Activities -- Chapter Seven. Technology Tools for Twenty-First-Century Learning -- Chapter Eight. Helping Students Become College and Career Ready.
'Staff Development for Educators.'
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching -- United States; Science -- Study and teaching -- United States